Uji Efektifitas Endomikoriza Indigenus terhadap Pertumbuhan Tanaman Jagung (Zea mays L.) - LELE, ONESIMUS KE; RAI, I NYOMAN; SUADA, I KETUT (Agrotrop : Journal on Agriculture Science; Vol 8 No 1 (2018)DO - 10.24843/AJoAS.2018.v08.i01.p03, 2018)
The Effectiveness Test of Indigenous Endomycorrhiza on Maize Plant Growth (Zea mays L.). Efforts to increase crop productivity were hampered due to various obstacles such as genetic, environmental, and biotic factors, in order that alternative technologies such as endomycorrhizal biological agents were required. This study was aimed to determine the effectiveness of indigenous endomycorrhiza for the growth of maize. The experiments were carried out in the laboratory and greenhouse. The field experiment was designed in a nested randomized block design. The first factor was genus of indigenous endomycorrhiza (M) consisting of 3 lavels i.e genus Glomus (G), genus Gigaspora (F) and the mixed genus (C), the second factor was the spore dose (D) consisting of 3 levels i.e. D1 = dose of 50 spores, D2 = 100 spores and D3 = 150 spores. The genus Glomus was able to increase the weight of fresh and dry oven total stalk, the number of leaves and the height of the plants and those significantly higher than that of the genus of Gigaspora and the mixed genus. Spore doses (50, 100 and 150 spores) of the genus Glomus and the genus Gigaspora and mixture gave no significant different results on all observed variables.